2021
DOI: 10.33003/fjs-2020-0404-502
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of an Intrusion Detection System Using C4.5 Machine Learning Algorithm

Abstract: The increasing growth of wireless networking and new mobile computing devices has caused boundaries between trusted and malicious users to be blurred. The shift in security priorities from the network perimeter to information protection and user resources security is an open area for research which is concerned with the protection of user information’s confidentiality, integrity and availability. Intrusion detection systems are programs or software applications embedded in sophisticated devices to monitor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…ey proposed an intrusion detection model based on the C4.5 algorithm. e outcomes showed that the typical identification pace of the model is 99.62%, and the misleading positive rate is diminished by 0.38% [6]. Gao et al concentrated on a twoventure harm conclusion structure for warm security frameworks in light of quantile irregular timberland and self-coordinating guide (SOM) brain organization.…”
Section: Related Workmentioning
confidence: 99%
“…ey proposed an intrusion detection model based on the C4.5 algorithm. e outcomes showed that the typical identification pace of the model is 99.62%, and the misleading positive rate is diminished by 0.38% [6]. Gao et al concentrated on a twoventure harm conclusion structure for warm security frameworks in light of quantile irregular timberland and self-coordinating guide (SOM) brain organization.…”
Section: Related Workmentioning
confidence: 99%